2009
DOI: 10.1111/j.1468-3083.2009.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based assessment of Mycoplasma genitalium in Vietnam – low prevalence among married women of reproductive age in a rural area

Abstract: The prevalence of M. genitalium among married women in Vietnam was relatively low. However, more large, well-designed and appropriately performed studies in other population groups including unmarried women and men, and in other geographical areas, rural as well as urban, are crucial in order to extract any evidence-based conclusions regarding the overall prevalence of sexually transmitted infections (STIs), including M. genitalium infections, in the Vietnamese society. The present study compiled with such fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
7
1
1
Order By: Relevance
“…The prevalence of M. genitalium in our study sample was higher than the prevalence reported for the general population in Denmark (24), Japan (25), Russia (22), Vietnam (21) and Peru (13) and was higher than the prevalence reported for most studies involving STI clinic attendees (26) and the general adolescent population (6) in the United States. However, it was still lower than the prevalence reported for STI clinic attendees in Russia (27) and sex workers in Kenya (28), Ghana and Benin (29).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The prevalence of M. genitalium in our study sample was higher than the prevalence reported for the general population in Denmark (24), Japan (25), Russia (22), Vietnam (21) and Peru (13) and was higher than the prevalence reported for most studies involving STI clinic attendees (26) and the general adolescent population (6) in the United States. However, it was still lower than the prevalence reported for STI clinic attendees in Russia (27) and sex workers in Kenya (28), Ghana and Benin (29).…”
Section: Discussioncontrasting
confidence: 87%
“…Positive results were confirmed by repeating the assay after repeated DNA extraction of the original specimen. All assays had an internal control for detection of PCR-inhibition and suboptimal reaction conditions (21,22). …”
Section: Methodsmentioning
confidence: 99%
“…We screened the titles and abstracts of 3,316 unique records published after 1991 and the full text of 833 studies (Figure S1 in online Appendix). A total of 63 records was included with participants who were; sampled at random from the general population [19][20][21][22][23][24] or using alternative community-based methods, [25][26][27][28][29] MSM and male-to-female transgendered, [30][31][32][33][34][35] FSW, [36][37][38][39][40] and pregnant women. [41][42][43][44] Of these, 37 studies included patients attending healthcare settings.…”
Section: Search Resultsmentioning
confidence: 99%
“…Oakeshott et al [12] demonstrated young age and race as risk factors for M. genitalium, in addition, majority of patients in the Baltimore study were African American. Olsen et al had a very low prevalence of M. genitalium among married Vietnamese women [13].…”
Section: Discussionmentioning
confidence: 99%